Band-Engineered α-Fe2O3@NiO P-N Heterojunction for Room-Temperature NH3 Detection and Real-Time Meat Spoilage Monitoring - Mingjia Li; Gaoshan Zeng; Haoyue You; Ding Xi; Hui Huang; Xin Kou; Amjad Farid; Yongpeng Zhao (Nanomaterials)
Recent advancements in biomarker technology have revolutionized diagnostic and monitoring applications, yet their potential in food quality assessment remains largely untapped. Herein, we report a breakthrough in gas-sensitive nanocomposite engineering through the design of α-Fe2O3-NiO heterostructures synthesized via a single-step hydrothermal protocol. The introduction of NiO led to increased oxygen vacancies and active sites, thereby reducing the sensor’s operating temperature. Additionally, the P-N heterojunction structure promoted the redistribution of electrons and hole, thus enhancing its conductivity. The optimized sensor exhibited high sensitivity (75.5% at 100 ppm), fast response/recovery (20 s/92 s), and perfect selectivity for NH3 at room temperature. In the end, based on this sensor and combined with a Programmable Logic Controller (PLC), a rapid and nondestructive meat spoilage detection system was constructed to reflect the degree of spoilage of meat with the help of NH3 concentration, providing a valuable strategy for the application of biomarker detection in the food industry.